Detection of numerous HIV-1/MO recombinants in France. (19th June 2018) - De Oliveira, Fabienne; Cappy, Pierre; Lemée, Véronique; Moisan, Alice; Pronier, Charlotte; Bocket, Laurence; Bouvier-Alias, Magali; Chaix, Marie-Laure; Gault, Elyanne; Morvan, Odile; Poveda, Jean-Dominique; Schneider, Véronique; et al.
Abstract : Background: The broad genetic divergence of HIV-1/O relative to HIV-1/M has important implications for diagnosis, monitoring and treatment. Despite this divergence, some HIV-1/M+O dual infections and HIV-1/MO recombinant forms have been reported, mostly in Cameroon, where both groups are prevalent. Here, we describe the characteristics of such infections detected in France in 10 new patients, and discuss their implications for biological and clinical practice, owing to the presence of group O species. Methods: The French National Reference Centre for HIV received samples within the framework of mandatory notification of HIV infections, and for expert analysis. A strategy combining serotyping, viral quantification, group-specific molecular amplification and whole-genome sequencing was used for strain characterization and complementary investigations. Results: We identified one patient with M+O infection, three patients with M+O infection associated with an MO recombinant, and six patients with only an MO recombinant. These atypical infections were detected upon strain characterization ( n  = 4) or because of anomalies during patient monitoring ( n  = 6). We identified eight new URF_MO, all but one originating from Cameroon. Interestingly, two distinct recombinant strains were found in two unrelated patients, representing possible precursors of a CRF_MO. Conclusion: Our work highlights the fact that the continuous evolution of HIV can hinder diagnosis and complicate clinical practice. We stress that unexpected results during diagnosis or monitoring necessitate further serological and molecular exploration, these atypical infections influence biological and therapeutic management and necessitate appropriate tools, and specific surveillance is necessary, especially as the frequency of such infections may be underestimated. Abstract : Supplemental Digital Content is available in the text